Smart driving assistance system using Raspberry Pi and actuator networks. Issue 1 (March 2021) - Ghani, Saiful Anwar Che; Kettner, Maurice; Aslan, Ferhat; Dzharuddin, Fatimah; Sazali, Norazlianie
Abstract: Testing and certification of vehicles in succession to their development are usually achieved on chassis dynamometer testbeds. This paper proposes the implementation of a smart real-time driving assistance system using cloud-computing, embedded tools and motorised actuator for vehicles with manual transmission powertrain under testing. For clutch actuation of the vehicle, a robotic leg actuator connected to a high torque stepper motor is controlled by Python code programmed on Raspberry Pi 4, linked through a smart network for remote controlling of the system via a user interface dashboard and digitalized working system so as to employ data connectivity through cloud-computing. By applying this network structure, the implementation functionality of smart driving assistance system using free cloud infrastructure is investigated, when the hardware is setup in Malaysia, whilst the control is from Germany. The framework that governs this prototype involves different domains of engineering such as data processing, manufacturing, mechanics, networking, embedded systems and actuators is able to be utilised in smart driving assistance system for car tested on a chassis dynamometer with latency of less than 1 s.